The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1016/j.mayocpiqo.2021.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Shock Severity Assessment in Cardiac Intensive Care Unit Patients With Sepsis and Mixed Septic-Cardiogenic Shock

Abstract: We sought to validate the Society for Cardiovascular Angiography and Interventions (SCAI) cardiogenic shock classification for mortality risk stratification in patients with sepsis and concomitant cardiovascular disease or mixed septic-cardiogenic shock. We conducted a single-center retropective cohort study of cardiac intensive care unit patients with an admission diagnosis of sepsis. We used clinical, vital sign, and laboratory data during the first 24 hours after admission to assign SCAI shock stage. We inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
3
6
0
1
Order By: Relevance
“…A recent publication has demonstrated that shock severity at admission is a predictor of worse one-year mortality. 27 This observation appears consistent with Hawkins et al 28 who suggested that a genomic or cytokine storm at the time of initial illness is a factor in the development of chronic critical illness. Moreover, it was recognized that 15% of patients did not develop PICS.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A recent publication has demonstrated that shock severity at admission is a predictor of worse one-year mortality. 27 This observation appears consistent with Hawkins et al 28 who suggested that a genomic or cytokine storm at the time of initial illness is a factor in the development of chronic critical illness. Moreover, it was recognized that 15% of patients did not develop PICS.…”
Section: Discussionsupporting
confidence: 85%
“…Since we found that ACS patients had a higher occurrence of these conditions, it may warrant further examination of degree of inpatient illness. A recent publication has demonstrated that shock severity at admission is a predictor of worse one-year mortality 27 . This observation appears consistent with Hawkins et al 28 who suggested that a genomic or cytokine storm at the time of initial illness is a factor in the development of chronic critical illness.…”
Section: Discussionsupporting
confidence: 72%
“…Our results are consistent with data obtained in previous studies, indicating that mortality was substantially higher among patients with SCAI stages D and E (75.2% and 88.3%, respectively), who were identified as having advanced hemodynamic and metabolic shock states at admission (lactic acidosis, renal impairment, and liver injury). The application of the SCAI shock stage to our study population showed high discrimination for 30-day mortality, similar to that reported by Jentzer et al (AUC, 0.65 vs 0.68) [18]. Another important finding is the very high mortality (70%) in the first 72 hours after admission in patients with shock stages D and E.…”
Section: Plos Onesupporting
confidence: 90%
“…Более того, в настоящее время получены свидетельства связи компонентов этой шкалы с нарушениями при сепсисе внутриклеточных сигнальных пу тей, изменениями уровня матричной и митохондриальной РНК [24]. Указывают, что кардиальная подшкала SOFA в первые 24 ч нахождения в ОРИТ может стратифицировать риск летальности у больных с сепсисом и сопутствующими сердечно-сосудистыми заболеваниями, а также при сочетании септического и кардиогенного шока [25]. Установленные в настоя щей работе ППК и ПЗ оценки по SOFA, указывающие на высокий риск летального исхода, практически совпали с результатами наиболее современных исследований, посвященных предикторной способности этой шкалы [26].…”
Section: Discussionunclassified